Stress Management Among Private Bank Employees (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Stress in the workplace, particularly in private banks, has become a critical concern due to the demanding nature of the job. This research paper investigates the sources of stress among private bank employees, its impact on their performance and health, and evaluates the effectiveness of various stress management strategies. A hypothesis test is conducted to determine whether middle-level employees experience significantly more stress than top-level employees. The findings provide insights into enhancing employee well-being and productivity.